The effect of potassium and mycorrhiza on growth of vanilla (Vanilla planifolia Andrew) - I GEDE TIRTA (Biodiversitas Journal of Biological Diversity, 2006)
The few and shallow roots caused slow growth of vanilla seedling. Mycorrhiza may increased the absorption of water and nutrients, while potassium may increased the rate of growth and strength of seedlings. This study was conducted at Sambangan Village, Buleleng, Bali in 2003 (April-Agustus 2003). The experiment was done in polybag and was arranged in Randomized Block Design with three replications. The treatments were consisted of two factors. The first factor was the rates of KCl fertilizer ( 0, 100 and 200 kg ha-1 or 0, 0,10 and 0,20 9 plant-1) and the second factor was the rates of mycorrhiza (0, 20 and 30 g plant-1). The aim of the research to study interactions between potassium and mycorrhiza and The optimum dosage the mycorrhiza on growth of vanilla (Vanilla planifolia Andrew). The resultes showed that there were interactions between potassium and mycorrhiza on fresh weight of the new shoot, root length and fresh root weight. The optimum dosage of the mycorrhiza was 20 g plant-1 with new shoot fresh weight was 25.63 g plant-1. The longest root (24.67 cm plant-1) was observed at the treatment without potasium with 20 g plant-1 mycorrhiza and this was 23% longer than control (19.93 cm plant-1). The highest fresh root weight (2.48 g plant-1 ) was observed at the dosage of 200 kg KCl ha-1 and 20 g mycorrhiza plant-1 and that was 55% heavier than control (1.60 g plant-1). The leaf number of the plant with 20 g plant-1 mycorrhiza was 6.22 and that was 18% more than control with leaf number 5.25. The total fresh weight of the seedling with 20 g plant-1 mycorrhiza was 86.74 g plant-1or 15% higher compared with control (75.18 g plant-1). The dosage of 100 kg KCl ha-1 increased the K content of the plant (2.45%K) or 35% higher than control (1.81%K). Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: Vanilla planifolia, growth, potassium, mycorrhiza.